It is all about quadratic equations

Algebra Level 2

Given that x = 5 x=-5 is a root to the quadratic equation 2 x 2 + p x 15 = 0 2x^2 + px - 15 = 0 . And the quadratic equation p ( x 2 + x ) + k = 0 p (x^2 + x) + k = 0 has equal roots. Find the value of k k .

1 3 \frac13 4 3 \frac43 3 9 \frac39 7 4 \frac74

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Sathvik Acharya
Feb 21, 2021

f ( x ) = 2 x 2 + p x 15 g ( x ) = p ( x 2 + x ) + k = p x 2 + p x + k \begin{aligned} f(x)&=2x^2+px-15 \\ g(x)&=p(x^2+x)+k=px^2+px+k\end{aligned} Since x = 5 x=-5 is a root of the quadratic f ( x ) f(x) , we have, f ( 5 ) = 0 2 ( 5 ) 2 + p ( 5 ) 15 = 0 p = 7 \begin{aligned} f(-5)&=0 \\ 2(-5)^2+p(-5)-15&=0 \\ \therefore \; p&=7 \end{aligned} Also, the quadratic g ( x ) = p x 2 + p x + k = 7 x 2 + 7 x + k g(x)=px^2+px+k=7x^2+7x+k has equal roots, implying that its discriminant must be zero. Δ = 0 7 2 4 7 k = 0 49 28 k = 0 \begin{aligned} \Delta& =0 \\ 7^2-4\cdot 7\cdot k&=0 \\ 49-28k&=0 \end{aligned} k = 49 28 = 7 4 \therefore \; k=\frac{49}{28}=\boxed{\frac{7}{4}}

Chew-Seong Cheong
Feb 22, 2021

Since x = 5 x=-5 is a root to 2 x 2 + q x 15 = 0 2x^2 + qx - 15 = 0 , 2 ( 5 ) 2 5 p 15 = 0 10 p 3 = 0 p = 7 \implies 2 (-5)^2 - 5p - 15 = 0 \implies 10 - p - 3 = 0 \implies p = 7 . Then we have:

p ( x 2 + x ) + k = 0 7 ( x 2 + x ) + k = 0 x 2 + x + k 7 = 0 ( x + 1 2 ) 2 1 4 + k 7 = 0 \begin{aligned} p(x^2 + x) + k & = 0 \\ 7(x^2 + x) + k & = 0 \\ x^2 + x + \frac k7 & = 0 \\ \left(x + \frac 12\right)^2 - \frac 14 + \frac k7 & = 0 \end{aligned}

For p ( x 2 + x ) + k = 0 p(x^2+x)+k = 0 to have equal roots of x = 1 2 x = - \dfrac 12 , k 7 = 1 4 k = 7 4 \implies \dfrac k7 = \dfrac 14 \implies k = \boxed{\frac 74} .

Kishore Ilayaraja
Feb 21, 2021

Hint : 2(-5)2 + p x ( -5) - 15 = 0 implies p = 7

Now, p(x2 + x ) + k = 0 ,, substitute the value of p in the equation

Apply, D = B2 - 4ac

Solution : p = 7 , k = 7/4

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...